'Decoupling' land productivity and greenhouse gas footprints: A review. (30th October 2018) - Wang, Li; Cutforth, Herb; Lal, Rattan; Chai, Qiang; Zhao, Cai; Gan, Yantai; Siddique, Kadambot H.M.
Abstract: A major challenge of our time is to produce sufficient nutrient‐rich food for the ever‐growing human population with limited land resources. There is a huge gap between current yields and genetic potential in many crops, which can be narrowed by enhancing land productivity. High‐input cropping increases crop yields, but heavy fertilizer and pesticide use can lead to land degradation, increase greenhouse gas footprint, and carry significant risks for eutrophication. What efforts can be taken to 'decouple' land productivity and the environmental footprint? Can land productivity increase while concurrently minimizing the environmental footprint? Here, we show that an integrated systems approach can minimize the tradeoff to achieve an effective 'decoupling' outcome. Some key components that can be integrated into a system include (i) intensifying crop rotations to enhance carbon conversion from atmospheric CO2 to plant biomass, (ii) diversifying cropping systems to enhance residual soil water and nutrient use and increase systems resilience, (iii) including N2 ‐fixing pulse crops in rotations to reduce synthetic fertilizer use, (iv) improving fertilizer‐N use efficiency to lower N2 O emissions, and (v) sequestering more carbon to the soil to potentially offset CO2 equivalent emissions from cropping inputs. Integration of these proven cropping practices into a system creates a powerful synergy among individual components, thereby improving land productivity and systems resilience for long‐term sustainability. Relevant economic and agro‐environmental policies are needed to reinforce the adoption of a systems approach at the local farm level.